Mainstreaming microfinance: balancing financial performance and outreach - Panditharathna, K.M.; Rajapakse, R.P.C.R. (University of Jaffna, 2024)
There is an unsolved dilemma in the Sri Lankan microfinance sector: whether microfinance institutions target low-income earners or seek profitability. To contribute to this debate, this research investigates the effect of financial performance on outreach and the effect of outreach on financial performance. Balancing financial performance and outreach of microfinance institutions have been conducted in various countries and regions, but specifically not for Sri Lanka after implementing No.06 of 2016 Microfinance Act. This study used an empirical data set for ten years, from 2010 to 2019. Data was collected from 16 MFIs and the panel data regression model was used for the analysis. According to the results MFIs can achieve financial and social objectives simultaneously when serving a larger number of customers and a high percentage of female borrowers. But providing services to the core poor people diminishes their financial performance. As per the findings, policy makers are required to make a roadmap to protect both customers and organization financial sustainability. This study emphasizes the importance of having a proper reporting system for the microfinance sector and future research may wish to consider more MFIs by considering a long period and future research can occupy financial performance and outreach variables which are good at forecasting.
Keywords: Financial Performance; Microfinance Institutions; Outreach; Panel Data; JEL Classification: G20, G21